MHC class II regulation by epigenetic agents and microRNAs - Tomasi, Thomas B. (2010)
MicroRNAs have been shown to regulate gene expression both transcriptionally and translationally. Here, we examine evidence that various stresses regulate miRNAs which, in turn, regulate immune gene levels. Multiple studies are reviewed showing altered microRNA levels in normal cells under stress and in various disease states, including cancer. Unexpected was the finding that Dicer expression is altered by treatments with several agents, such as interferons and cortisone, employed in the treatment of immune disorders. Potential signal transduction pathways, including JAK/Stat, PI3K and PKR, that may regulate Dicer and microRNA levels in normal and stressed mammalian cells are discussed.